Implications of Facial Asymmetry in Rhinoplasty. Issue 3 (September 2017) - Rohrich, Rod J.; Villanueva, Nathaniel L.; Small, Kevin H.; Pezeshk, Ronnie A.
Abstract : Summary: Many rhinoplasty patients present with a chief complaint of nasal deviation and are unaware of any inherent facial asymmetries; however, recognizing and discussing the interrelation between the deviated nose and facial asymmetry is an important consideration in surgical planning. The objective of this study was to evaluate whether a surgeon's subjective assessment of facial analysis in the setting of nasal deviation correlates with objective anthropometric measurements. In addition, this study sought to further quantify the frequency of facial asymmetry associated with nasal deviation to highlight important anatomical trends for the rhinoplasty surgeon. Finally, this study presents the senior author's (R.J.R.) method of addressing a deviated nose on an asymmetric face. In this study, the authors demonstrated that nasal deviation is closely related to facial asymmetry. Furthermore, the authors demonstrated that objective facial analysis closely correlates to anthropometric facial measurements. In addition, the wide side of the face correlates to the short side of the face and the nose tends to deviate away from the wide side of the face. During surgical correction of the deviated nose in the setting of facial asymmetry, the surgeon's goal should be to obtain nasal symmetry and center the nose on a line between the mid glabella and the mid Cupid's bow. This may reduce the perception of a facial asymmetry, leading to increased patient satisfaction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV.